The Impact of the Educational Differences on the Workers Mobility on the Russian Labor Market - ОльбиковаЕвгения Ивановна (Journal of Economic Sociology, 2010)
The main goal of the paper is to identify the impact of the educational level on the type of the inter-firm workers mobility. The basic assumption is that the level of education strongly influences the labour market segmentation that is why the education should have certain impact on the type of the workers’ mobility. The data analysis based on RLMS gives the contradictory results. On the one hand the level of education determines the chances to be unemployed or non-active. On the other hand the level of education has impact on the probability of the inter-firm workers’ mobility only for males of 22-45 years old. Moreover upward mobility in terms of wages was true only for man but the level of education was not significant for this.